Evaluation of adaptability and stability for iron, zinc and protein content in cowpea genotypes using GGE biplot approach - Araújo, Mauricio dos Santos; Lelis de Aragão, Walter Frazão; Pinheiro dos Santos, Samiria; Teixeira Freitas, Thaise Kessiane; da Costa Saraiva, Verônica; de Moura Rocha, Maurisrael (Elsevier, 2022)
Cowpea is a widely cultivated crop in the world. Biofortification strategies aim to reduce mineral and protein deficiencies, especially among the poorest people. The aim of this study was to estimate adaptability and stability of cowpea genotypes for iron, zinc and protein contents, through GGE biplot analysis. Twenty cowpea genotypes were evaluated in the municipalities of Piauí Monsenhor Hipólito, Pio IX and São Miguel do Tapuio, under rainfed conditions. The experimental design was a randomized block design with four replications. The traits evaluated were grain yield, iron, zinc and protein contents in dry grains. Iron (Fe) and zinc (Zn) were determined by flame atomic absorption spectrophotometer, and protein contents by Kjeldahl methods. Adaptability and stability were evaluated by GGE biplot analyses. The means of the experiments were 1,209.1 kg ha−1, 51.1 mg kg−1, 46.8 mg kg−1 and 24.3% for grain yield, Fe, Zn and protein contents, respectively. The joint analysis of variance showed significant difference (p < 0.05) for the effect of interaction genotypes by environments for Fe, Zn and protein contents. The lines G6 and G8 were the most promising for grain yield, mineral and protein content through adaptability and stability by GGE biplot approach.